THE AN ANALYSIS OF STUDENT TEACHER’S PERSPECTIVE AND PRACTICE AT STKIP MUHAMMADIYAH ACEH BARAT DAYA - Julia; Sukri Adani (Yayasan Nusantara Hasana Berdikari, 2023)
Teaching experience has a high contribution to many aspects of effective teaching. Through experiences, teachers learn to conquer different teaching strategies, manage classrooms, and improve their professionalism in the field. Higher education students are given the chance to have a pre-work experience known as teacher practice or Student-Teacher Practice Program. At STKIP Muhammadiyah, in their third year of study, students are required to join this program which becomes their chance and venue to apply the learned theories to practical work. The current study, therefore, aimed to describe the student’s perception, and practice of the teacher practice at the lower school level. Further, these experiences were described and categorized to see how students perceive the experience and how it contributes to their teaching competence. This research used a descriptive qualitative design. The data was collected through an interview protocol. The sources of data were the 7th-semester students of STKIP Muhammadiyah Aceh Barat Daya who joined the program. The finding of the research revealed that student teachers’ perspectives and practices of teaching experience are positive. Teaching practices gave them lots of positive experiences, and help them to understand real classroom situations and students’ character. Furthermore, the research was expected to give a significant contribution to students, teachers, or researchers who were interested in a similar issue.